Acculturation stress and allostatic load among Mexican immigrant women - D’Alonzo, Karen Therese (Escola de Enfermagem de Ribeirão Preto / Universidade de São Paulo, 2019)

(untitled) (Rev Lat Am Enfermagem)
OBJECTIVES: this case-control study compared levels of stress and allostatic load (AL) among Mexican women in the US ( n =19) and Mexico ( n = 40). METHOD: measures of stress included the Perceived Stress Scale (PSS) and the Hispanic Women’s Social Stressor Scale (HWSSS). A composite measure of 8 indicators of AL (systolic and diastolic blood pressure, body mass index (BMI), waist-to-hip ratio, total cholesterol, glycated hemoglobin (hemoglobin A1C), triglycerides and C-reactive protein) was calculated. RESULTS: there were no significant group differences in AL between Mexican and Mexican immigrant women ( t = 1.55, p = .126). A principal component factor analysis was conducted on the 8 AL indicators; a 2-factor solution explained 57% of the variance. Group differences in the two AL factors were analyzed using MANOVA. BMI and waist-to-hip ratios were lower, but blood pressure and triglycerides were higher in the US group and were mediated by time in the US. Greater acculturation stress was significantly related to increased waist-to-hip ratio ( r = .57, p = .02). FINAL REMARKS: findings suggest some measures of AL increased with time in the US, and acculturation stress may be a significant factor.